Epidemiological aspects of pediculosis by Pediculus humanus capitis (Phthiraptera: Pediculidae) in Minas Gerais: a systematic review - Pedro Alves Soares Vaz de Castro; Laura Silva Paranhos; Grasielle Caldas D'Ávila Pessoa; David Soeiro Barbosa; Mariângela Carneiro; Juliana Maria Trindade Bezerra (Instituto de Estudos em Saúde Coletiva da Universidade Federal do Rio de Janeiro, 2023)
Abstract Background Head lice, or head pediculosis, is a parasitosis considered a serious public health problem that affects mainly resource-limited countries. Objective To describe epidemiological aspects of the pediculosis capitis in Minas Gerais, in Brazil. Method This systematic review was conducted through the standards established by the Preferred Reporting Items in Systematic Reviews and Metanalyses (PRISMA). PubMed, LILACS, and SciELO databases, as well as the gray literature, were searched. Results Nine of 1,167 studies were included, published between 1988 and 2019. These studies reported a total prevalence of parasitosis that ranged from 1.4% to 57.4%. The prevalence of head lice ranged from 0.0% to 66.7% for males and 2.3% to 57.4% for females, thus being higher in black-skinned people (1.4% to 40.3%). Regarding age, the highest prevalence was 10-12 years old (45.3%). As for the characteristics of the hair, there was a greater infestation in people with long (16.0% to 79.5%), wavy (0.0% to 44.7%), dark (0.0% to 36.6%), with low capillary density (35.4%), and thick hair (39.2%). Conclusion Head pediculosis affects both sexes, different ages, and races, representing an important health problem in Minas Gerais, not only due to the presence of ectoparasite but also to the secondary complications that can be generated from this parasitism.